The mystery of the book of Revelation: reenvisioning the end of time - Afzal, Cameron (Hors serie, 2008)
Introduction -- Reading time : a matter of method -- The communal icon -- The experience of time -- Inscribed time -- Apocalypse and prophecy -- The literary genre apocalypse -- The apocalypse as prophecy -- John and his community -- Who was John? -- The occasion for John's prophecy -- A vision of this world in six seals -- The introductory Merkavah vision -- Experienced catastrophe -- The four horsemen : a symbolic year -- The fifth seal : the plight of the faithful -- The sixth seal : the signs of the end -- Sabbath : a new age -- A window in time -- The followers of the Lamb